Influência da interação hidroclorito de sódio e clorexidina sobre a adesão de cimentos endodônticos resinosos - Leal, Luciana Oliveira (2012)
The purpose of this study was to evaluate, ex vivo, the influence of the precipitate formed by the association between sodium hypochlorite and chlorhexidine on the adhesion of resin-based sealer to root dentin. For this, we used push out test and analysis of fracture pattern in stereomicroscope. Sixty-four extract-ed single-rooted human teeth had their crowns removed and the diameter of the channels was standardized. The teeth were randomly divided into four groups ac-cording to the intracanal medication used: no medication (Ctrl), 2% chlorhexidine gel (CHX-G), 2% chlorhexidine solution (CHX-S), 2% chlorhexidine solution with surface modifiers sodium lauryl ether sulfate (CHX-L). The samples were divided into four subgroups and filled with Sealer 26 ® (S26), AH Plus ® (AHP) EndoREZ ® (ER), Real Seal ® (RS). After seven days, the roots were sectioned in 1 mm thick-ness discs (n = 16) and they were subjected to push out test (1 mm / min). We ap-plied Anova / Tukey (1%). The fonts of variation medication and cement versus medication did not show statistical difference (p <0.01). When analyzed the factor cement, RS showed the lowest values, with statistical difference compared to other sealers (p <0.01). The stereomicroscope analysis (40X) showed that S26 has present-ed predominantly cohesive failure being 70% in Ctrl.S26 and 100% in others. AHP showed 50% cohesive failure in CHX-G.AHP and CHX-L.AHP; 61.11% in Ctrl.AHP and 78.5% in CHX-S.AHP. The methacrylate-based cements ER and RS showed predominantly adhesive failures, except CHX-S.ER, which showed 64.28% cohesive failure. Two samples for each group ware analyzed by scanning electron microscopy (SEM). It can be concluded that the interaction between sodium hypo-chlorite and chlorhexidine had no effect on the bond strength of the push out of resin-based sealer to root dentin